Analysis of Financial Literacy in Families Receiving the Family Hope Program (PKH) Benefits in Bogor Regency - Ferry Ando; Nana Sulaksana; Heru Nurasa (Eduvest - Journal of Universal Studies, 2025)
This study examines financial literacy among families receiving benefits from the Program Keluarga Harapan (PKH) in Bogor Regency, Indonesia. Despite government efforts to reduce poverty through initiatives such as PKH, persistent issues of financial mismanagement highlight the ongoing need for enhanced financial literacy to improve household welfare. The research aims to assess the level of financial literacy, identify its determinants, and analyze its impact on financial behaviors and family well-being. Employing a quantitative methodology, data were collected from 399 beneficiary families using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial literacy has a significant effect on financial decision-making, financial skills, and financial behaviors, with financial awareness and financial experience identified as key influencing factors. The study emphasizes the critical role of financial education in empowering beneficiaries to manage social assistance more effectively, thereby contributing to improved family welfare. Practical implications include recommendations for the development and implementation of targeted financial literacy programs designed to strengthen the financial capabilities of PKH recipients